Methodology based on problem solving in the treatment of the concept of limit to infinity (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2014)
In this research, a methodological strategy it is raised for the assimilation of the concept of infinity limit in the teaching and learning of calculus at the University level. The strategy considers the contributions and theoretical elements of dialectical materialism and methodological elements and relies on the contributions of activity theory, problem solving and concept formation. It is wise to suggest that problem solving played central role in the process of assimilation of the concept of limit to infinity.